Teaching of technical and architectural drawing: a proposal for interdisciplinary exercises of graphic representation (Research, Society and Development, 2019)
The work served to support the construction of an educational product, a book of contextualized exercises of technical and architectural design. The research was qualitative and quantitative. The theoretical basis was based on interdisciplinarity in teaching, focusing on teaching drawing. Under the methodological aspect, it is a research with strategy of the type design science. In the work, strategies were created to facilitate the learning of drawing education by the accomplishment of exercises more attractive and contextualized, close to the reality of the students; the contributions of the book in the teaching-learning process were verified and the importance of interdisciplinarity among related areas such as civil engineering and architecture was verified. The first version of the book was evaluated in the process of content validation by judges and, by pedagogue, through didactic-pedagogical evaluation. Finally, a graphical exercise book was presented that uses the architectural historical context of buildings to understand the elements of the existing architecture and, in order to attract students and to approach the contents of the course, the demonstration of the structural systems. The exercises were relevant and the format of the book, clear and objective, adding knowledge about the buildings. It follows a methodological course that will guarantee the applicability in the academic reality, will allow the development of the space vision of the students if there is training and will collaborate with the approximation of the reality of the course in Civil Engineering, being able to be applied also in the course of Architecture and technical course in Buildings.